Electrochemical impedance spectroscopy of thiourea electro-oxidation on copper electrodes in aqueous 0.5 M sulphuric acid - Gassa, Liliana Mabel (2002)
The anodisation of copper electrodes in aqueous thiourea (TU) containing 0.5 M sulphuric acid is studied by electrochemical impedance spectroscopy (EIS) combined with rotating disk electrode and ring-disk electrode, SEM and EDAX techniques. For E<−0.35 V (vs. MSE), Nyquist plots show two time constants. The first one, which appears at high frequencies, involves the contribution of the double layer capacity and the charge transfer resistance related to the electro-oxidation of TU to formamidine disulphide (FDS). The second time constant, which is observed at low frequencies, is related to complex electrochemical and chemical processes following TU electro-oxidation to FDS. Depending on the applied potential, this time constant can be assigned to either an electroadsorption process from TU electro-oxidation products or an electrochemical process under diffusion through an anodic film. At high TU concentration, the low frequency time constant corresponds to the typical response of a pure capacitor due to the formation of a thick anodic film under a diffusion controlled process. In this case, for E≥−0.35 V, Nyquist plots exhibit at least three time constants and an inductive loop. The inductive loop is due to surface relaxation associated with copper pitting. The formation of different types of anodic films is confirmed by SEM observations. EIS results are consistent with the complex reaction pathway previously proposed for the anodisation of copper in aqueous TU-containing acid solutions.